The Role of Clinical Instructors in Preventing Adverse Events Among Nursing Students - Diwa Agus Sudrajat; Nida Yunia Wardani (STIKep PPNI Jawa Barat, 2026)
Background: Patient safety is a fundamental aspect of healthcare delivery and a major concern in nursing education, particularly during students’ clinical practice, which carries a high risk of adverse events. Nursing students are in a transitional phase from theoretical learning to real clinical practice and therefore require adequate supervision to prevent clinical errors that may compromise patient safety. Objective: This study explored how clinical instructors perceive and enact their role in preventing adverse events during students’ clinical practice. Methods: A qualitative study with a descriptive phenomenological approach was conducted. Data were collected through in-depth semi-structured interviews with five clinical instructors who supervised nursing students across various hospital care units. The data were analyzed using thematic analysis to identify patterns of meaning related to clinical supervision and patient safety practices. Results: The analysis revealed that clinical instructors operate not only as supervisors but also as safety gatekeepers. Their role extends across several domains, including direct supervision, assessment of student readiness, real-time correction of unsafe practices, and modeling of professional behavior. Adverse events were largely viewed as preventable, but only when supervision was consistent and context-aware. Organizational factors, particularly workload and collaboration, shaped how effectively instructors could perform this role. Conclusion: Clinical instructors occupy a critical position at the intersection of education and patient safety. Strengthening their role requires not only individual competence but also institutional support and realistic workload structures.